MEMBEDAH TEORI PENEBUSAN KRISTUS: SEBUAH KAJIAN BIBLIKA - Buyung, Yopie F.M.; Nggebu, Sostenis; Soerjaman, Hertina; Bollu, Paulus (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2024)
The issue discussed in this article is the emergence of various views on the atonement of Christ. This problem causes differences in interpretation and application in Christian life. The purpose of writing this theme is to explain the issue of Christ's atonement and to put forward the attitude and view of the Bible regarding the biblical principle of atonement. The research method used is Biblical research. The result shows that the atonement of Christ is God's decree so that humans are redeemed and saved from the punishment of sin through Jesus' death on the cross and His resurrection from the dead. In conclusion, Christ Himself willingly took the place of sinful humans so that they might be saved by Him.